An Analytical Study of Causing Crimes: A Study Conducted at Sargodha & Shahpur Jails - Ali, Shahzad; Mahmood, Babak; Sohail, Malik Muhammad (Asian Journal of Empirical Research, 2012)
The study was conducted to analyze the causes and socio-economic factors that are possibly responsible for crimes in Pakistan. Crimes have always overwhelmed every society in human history. The history of crime is as old as history of mankind. The present study was conducted on the prisoners of Sargodha and Shahpur jails. Major constructs were i.e. socio-economic factors and unemployment. 200 respondents were selected, 100 from each jail. A well structured interview schedule was used to collect the data. Certain statistical techniques were used to reduce and analyze the data. Results show that majority of the respondents said that weak structure of judiciary and administration promotes crimes. Findings show that more than half of the respondents said that property is the main cause of crimes. Results of the study show that most of the respondents were agreed that unemployment is responsible from the crime in society. Overall situation was alarming; mostly crimes were committed because of poor socio-economic condition among prisoners at Sargodha and Shahpur jails.